How to integrate Design Thinking in the Verification and Validation of Software´s Life Cycle for Flight Simulators - Filoniuk, Valeria Raquel (2023)
In order to ensure the Flight Simulator´s functionality, this article exposes the application of the “Design Thinking” Methodology. This will lead to provide more creative and innovative solutions during the Verification and Validation process in the Flight Simulator Software´s Life Cycle. The application of this method in the first stages of the process allows an active and early interaction with user´s needs, increasing the building of solutions and the identification of needs, heighten the final product´s standards. It is important to ensure quality in the software development of flight´s simulators, due to its application is crucial and essential to the air defense of our country. So as to improve the aforementioned process, Design Thinking works with three main scenarios: Ideation, Inspiration and Implementation. The main objective of this article is to integrate these scenarios with the Verification and Validation of the Software´s Life Cycle and develop a new way to test software, including the user as a strategic source. It is expected that the results will contribute to create high quality products being these vital assets for the pilot´s training process who daily assume the challenge of guarding the Argentine sky.